2017
DOI: 10.1002/rra.3164
|View full text |Cite
|
Sign up to set email alerts
|

Large‐bodied fish assemblage characteristics in large rivers across Ontario

Abstract: Large-bodied fish assemblages were assessed in large rivers across Ontario. The objectives of this study were to (i) determine if there were relationships in large-bodied fish species within rivers;(ii) determine what factors explain the variability in the abundance of large-bodied fish within rivers across Ontario; and (iii) assessed variation in large-bodied fish biodiversity among these river.Standardized index netting was conducted at 22 sites across 12 major rivers and sampled 3889 fish representing 26 sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…The sampling techniques were identical among these studies therefore permitting the comparison of relative abundance. This study supported that S. canadensis are common in large, shallow rivers (Bozek, Haxton, & Raabe, ) whereas at a landscape scale, they demonstrated proclivity to deep, high‐discharge river (Haxton et al, ) and were not as abundant. This study also corroborated the ubiquity of S. vitreus population across Ontario (Haxton et al, ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The sampling techniques were identical among these studies therefore permitting the comparison of relative abundance. This study supported that S. canadensis are common in large, shallow rivers (Bozek, Haxton, & Raabe, ) whereas at a landscape scale, they demonstrated proclivity to deep, high‐discharge river (Haxton et al, ) and were not as abundant. This study also corroborated the ubiquity of S. vitreus population across Ontario (Haxton et al, ).…”
Section: Discussionsupporting
confidence: 74%
“…Relative abundance of S. canadensis and S. vitreus were similar in the Rainy River. CPUE of both species was greater than observed in the Ottawa River (Haxton, ), whereas the CPUE of S. canadensis was greater than observed in most rivers sampled in Ontario; S. vitreus CPUE was within the range reported (Haxton et al, ). The sampling techniques were identical among these studies therefore permitting the comparison of relative abundance.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…near to the Sturgeon Falls HGS, proximal to which suitable spawning habitat occurs) while older juveniles were more abundant further downstream. A similar size/age distribution of juveniles (smaller juveniles located in upstream reaches) was observed among eight reaches of the Seven Sisters Falls Reservoir on the Winnipeg River (Barth & Anderson, ), whereas the opposite (larger sturgeon closer to upstream spawning sites and smaller juveniles in areas distant from spawning areas) has been observed in the Attawapiskat River (Haxton, Friday, Cano, & Hendry, ), Ottawa River (Haxton, ) and the St. Lawrence River (Mailhot, Dumont, & Vachon, ). Based on the finding that juveniles rarely move among reaches separated only by rapids (Barth, Anderson, Henderson, & Peake, ), Barth and Anderson () suggested that the distribution of juveniles in the Seven Sisters Reservoir on the Winnipeg River was likely determined prior to age‐1, driven by non‐random patterns of larval drift (likely influenced by hydraulic conditions, which would vary among years) or differential larval mortality (higher rates of larval or young YOY mortality distant from spawning areas).…”
Section: Discussionsupporting
confidence: 62%
“…Based on the finding that juveniles rarely move among reaches separated only by rapids (Barth, Anderson, Henderson, & Peake, ), Barth and Anderson () suggested that the distribution of juveniles in the Seven Sisters Reservoir on the Winnipeg River was likely determined prior to age‐1, driven by non‐random patterns of larval drift (likely influenced by hydraulic conditions, which would vary among years) or differential larval mortality (higher rates of larval or young YOY mortality distant from spawning areas). Assuming the premise that distance of larval drift is a function of hydraulics (water velocity) (Benson, Sutton, Elliott, & Meronek, ) and is transferrable among systems, it was hypothesized that the observed differences in spatial segregation of life stages among systems may be due to their regulated/unregulated nature, wherein a high proportion of larvae would drift farther from spawning sites in unregulated systems (Haxton et al, ). Although water velocity was not measured during this study, field crews working during spring qualitatively assessed velocities as <0.2 m/s in all reaches downstream of Reach 1 (North/South Consultants Inc., unpublished data) when the river was experiencing spring discharges of 50–75 m 3 /s.…”
Section: Discussionmentioning
confidence: 99%